High‐throughput, microscope‐based sorting to dissect cellular heterogeneity - Hasle, Nicholas; Cooke, Anthony; Srivatsan, Sanjay; Huang, Heather; Stephany, Jason J; Krieger, Zachary; Jackson, Dana; Tang, Weiliang; Pendyala, Sriram; Monnat, Raymond J; Trapnell, Cole; Hatch, Emily M; et al. (Molecular systems biology, 2020)
Microscopy is a powerful tool for characterizing complex cellular phenotypes, but linking these phenotypes to genotype or RNA expression at scale remains challenging. Here, we present Visual Cell Sorting, a method that physically separates hundreds of thousands of live cells based on their visual phenotype. Automated imaging and phenotypic analysis directs selective illumination of Dendra2, a photoconvertible fluorescent protein expressed in live cells; these photoactivated cells are then isolated using fluorescence‐activated cell sorting. First, we use Visual Cell Sorting to assess hundreds of nuclear localization sequence variants in a pooled format, identifying variants that improve nuclear localization and enabling annotation of nuclear localization sequences in thousands of human proteins. Second, we recover cells that retain normal nuclear morphologies after paclitaxel treatment, and then derive their single‐cell transcriptomes to identify pathways associated with paclitaxel resistance in cancers. Unlike alternative methods, Visual Cell Sorting depends on inexpensive reagents and commercially available hardware. As such, it can be readily deployed to uncover the relationships between visual cellular phenotypes and internal states, including genotypes and gene expression programs. Synopsis This study describes an imaging‐based approach for pooled genetic screening and morphology‐based transcriptomics that uses high‐throughput photoactivation followed by FACS to separate differentially labeled cells. Expression of the photoactivatable fluorescent protein Dendra2 permits selective, irreversible, and high‐throughput labeling of cells exhibiting different visual phenotypes. These labeled cell subpopulations can be sorted and thus subject to diverse downstream genomics assays. Photoactivation using a digital micromirror device affixed to a 405 nm laser is accurate, non‐toxic, and can be tuned to produce four discrete levels of fluorescence. Human cells expressing sequence variant libraries can be sorted according to a visual phenotype followed by sequencing, which provides sequence‐function maps for phenotypes such as protein subcellular localization. Cell populations that respond in a visually heterogeneous fashion to drug treatment can be sorted and subject to transcriptomic analyses, revealing the molecular states associated with complex drug responses. Graphical Abstract This study describes an imaging‐based approach for pooled genetic screening and morphology‐based transcriptomics that uses high‐throughput photoactivation followed by FACS to separate differentially labeled cells.